Sustainable Yield of Threadfin Bream (Nemipterus sp.) Landed at Belawan Ocean Fishing Port, North Sumatra - Oktavia Sihombing; Septy Heltria; Nelwida Nelwida; Lisna Lisna; Fauzan Ramadan; Yusyam Leni (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2026)
Threadfin bream is a demersal fishery commodity landed at Belawan Ocean Fishing Port (PPS Belawan) and requires sustainable management due to fluctuations in fishing intensity. This study aimed to analyze the maximum sustainable yield, total allowable catch, utilization rate, and fishing effort rate of threadfin bream landed at PPS Belawan. The study was conducted from January 12 to 31, 2026, using secondary data on production and fishing effort from 2021 to 2025. The analysis included fishing gear standardization using the Fishing Power Index (FPI), Catch Per Unit Effort (CPUE) calculation, and maximum sustainable yield estimation using the Schaefer and Fox models. The results showed that bagged fish trawl (Jaring Hela Ikan Berkantong/JHIB) was selected as the standard fishing gear because it had the highest productivity. The Schaefer model estimated an MSY of 4,941.22 tons/year with an Fopt of 1,011.99 trips/year, while the Fox model estimated an MSY of 2,536.73 tons/year with an Fopt of 698.12 trips/year. The utilization rate ranged from 15% to 43%, with an average of 26%, indicating no production-based overfishing. However, fishing effort in 2024 and 2025 exceeded Fopt; therefore, fishing effort control is necessary.